Bias Gender Pembelajaran Pendidikan Agama di Aceh - Mardin M Nur (BUANA GENDER : Jurnal Studi Gender dan Anak, 2018)
This research would like to discuss about the behavior of teachers in the class against their behavior outside the classroom. Data collection techniques were obtained, unstructured interviews, documentary and triangulation studies using sexual theories. After doing research by using univariate and bivariate analysis, it can be concluded that the behavior of teachers in the class has a significant effect on their behavior outside the classroom. This is confirmed by data from the age of gender bias dimensions studied, eight dimensions (80%) occur in gender bias and two dimensions (20%) do not occur gender bias. There was a strong enough change between the two (100%). This means that the higher the gender bias in learning, the higher the gender bias and gender inequities in schools. This study discusses the relationship between gender bias of learning with bias and gender inequality in schools.